The Use of Personal Deixis in The Netflix Series “Losmen Bu Broto The Series” in 2025 - Herawati, Yuke Elvin; Sucipto; Padmasari, Arumtyas Puspitaning (Universitas Cokroaminoto Palopo, 2025)
In this study using a serial film that can be focused on conversations containing deixis phenomena in the Netflix serial film